A Comprehensive Review on Graphitic Carbon Nitride for Carbon Dioxide Photoreduction. Issue 12 (6th November 2022) - Khan, Javid; Sun, Yanyan; Han, Lei
Abstract: Inspired by natural photosynthesis, harnessing the wide range of natural solar energy and utilizing appropriate semiconductor‐based catalysts to convert carbon dioxide into beneficial energy species, for example, CO, CH4, HCOOH, and CH3 COH have been shown to be a sustainable and more environmentally friendly approach. Graphitic carbon nitride (g‐C3 N4 ) has been regarded as a highly effective photocatalyst for the CO2 reduction reaction, owing to its cost‐effectiveness, high thermal and chemical stability, visible light absorption capability, and low toxicity. However, weaker electrical conductivity, fast recombination rate, smaller visible light absorption window, and reduced surface area make this catalytic material unsuitable for commercial photocatalytic applications. Therefore, certain procedures, including elemental doping, structural modulation, functional group adjustment of g‐C3 N4, the addition of metal complex motif, and others, may be used to improve its photocatalytic activity towards effective CO2 reduction. This review has investigated the scientific community's perspectives on synthetic pathways and material optimization approaches used to increase the selectivity and efficiency of the g‐C3 N4 ‐based hybrid structures, as well as their benefits and drawbacks on photocatalytic CO2 reduction. Finally, the review concludes a comparative discussion and presents a promising picture of the future scope of the improvements. Abstract : This review comprehensively introduces the fundamental understanding of graphitic carbon nitride‐based materials for carbon dioxide photoreduction along with approaches to improve the photocatalytic properties, including elemental doping, structural modulation, surface functional group modification and heterojunction systems. A comparative discussion and promising picture of the future scope of the improvements are also provided.